2023
DOI: 10.3847/1538-4357/acee67
|View full text |Cite
|
Sign up to set email alerts
|

The Third Fermi Large Area Telescope Catalog of Gamma-Ray Pulsars

D. A. Smith,
S. Abdollahi,
M. Ajello
et al.

Abstract: We present 294 pulsars found in GeV data from the Large Area Telescope (LAT) on the Fermi Gamma-ray Space Telescope. Another 33 millisecond pulsars (MSPs) discovered in deep radio searches of LAT sources will likely reveal pulsations once phase-connected rotation ephemerides are achieved. A further dozen optical and/or X-ray binary systems colocated with LAT sources also likely harbor gamma-ray MSPs. This catalog thus reports roughly 340 gamma-ray pulsars and candidates, 10% of all known pulsars, compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 332 publications
0
26
0
Order By: Relevance
“…In the 13 4FGL fields, eight LAT sources have been associated with γ-ray pulsars (discovered after our CXO programs were approved) that were detected in the third Fermi LAT catalog of γ-ray pulsars (3PC; see Table 4; Clark et al 2015Clark et al , 2017Smith et al 2023). Two of the γ-ray pulsars, PSR J1906+0722 and PSR J1105-6037, have been relatively well studied, and their positions are known very precisely (Clark et al 2015(Clark et al , 2017.…”
Section: Counterparts Of Fermi Lat Sourcesmentioning
confidence: 99%
See 4 more Smart Citations
“…In the 13 4FGL fields, eight LAT sources have been associated with γ-ray pulsars (discovered after our CXO programs were approved) that were detected in the third Fermi LAT catalog of γ-ray pulsars (3PC; see Table 4; Clark et al 2015Clark et al , 2017Smith et al 2023). Two of the γ-ray pulsars, PSR J1906+0722 and PSR J1105-6037, have been relatively well studied, and their positions are known very precisely (Clark et al 2015(Clark et al , 2017.…”
Section: Counterparts Of Fermi Lat Sourcesmentioning
confidence: 99%
“…4.1.3. 4FGL J1104.9-6037 4FGL J1104.9-6037 has been associated with the γ-ray pulsar PSR J1105-6037, identified by the 3PC (Clark et al 2017;Smith et al 2023). A potential X-ray counterpart, 1SXPS J110500.3-603713, was reported in Wu et al (2018), with an observed flux of 2.5 10…”
Section: Smith Et Al 2023)mentioning
confidence: 99%
See 3 more Smart Citations